Estimation of Sediment Hydraulic Conductivity in River Reaches and its Potential Use to Evaluate Streambed Clogging. (3rd June 2014) - Datry, T.; Lamouroux, N.; Thivin, G.; Descloux, S.; Baudoin, J. M.
Abstract Streambed substrates have pervasive effects on stream biodiversity and biogeochemistry. The excessive input of fine sediments in streams and the subsequent alteration of the physical characteristics of streambed substrates are considered today as a major environmental issue. The estimation of streambed hydraulic conductivity (K) may be simpler than other estimations of reach‐scale physical characteristics and could serve to quantify the alterations of streambeds across stream networks. In this study, we examined between‐reach and within‐reach variability and temporal changes of streambed K across 101 stream reaches in France, including nine reaches previously judged as clogged and nine as references (unclogged). We also examined the relationships between K and some environmental variables such as vertical hydraulic gradient, streambed grain size, flow velocity or distance to the bank. We demonstrated that 15 measurements of streambed K per reach could be used to compare streams among each other and over time. Clogged reaches displayed much lower K than reference reaches, and more generally, reach‐averaged K and the number of non‐null K values per reach allowed discriminating reaches among each other without observer bias. K was higher in upwelling compared with downwelling areas, probably because of fine sediment uplifting. With the low cost in terms of equipment (<€100 per unit) and time (2–4 h per site), reach‐scale streambed K estimates are promising for studying the alterations of streambed substrates across stream monitoring networks such as clogging, but also for understanding large‐scale drivers of these alterations, or for upscaling recent developments in hyporheic ecology at the reach scale. Copyright © 2014 John Wiley & Sons, Ltd.